Implementation of Tourism Marketing Policy (Study of Culture and Tourism Office of North Lombok Regency, West Nusa Tenggara) - Siti Atika Rahmi; Agus Suryono; M. Makmur; Siti Rochmah (Wacana Journal of Social and Humanity Studies, 2021)
This research was conducted at the Culture and Tourism Office of North Lombok Regency of West Nusa Tenggara with the title Implementation of Tourism Marketing Policies. Qualitative research with methods used observation, interviews, and secondary studies to obtain data about tourism in North Lombok Regency. Tourism marketing that has been carried out by the Culture and Tourism Office is by participating in exhibitions on Lombok Island and outside the region. As well as collecting data on the number or number of tourists coming to the North Lombok Regency in the hope that these tourist numbers can be used to determine the tourism market share of North Lombok Regency. The marketing policy carried out is not yet effective and not yet on target so cooperation between the private sector in tourism marketing in North Lombok is needed.